2000
DOI: 10.2176/nmc.40.295
|View full text |Cite
|
Sign up to set email alerts
|

Inunediate Surgery Reduces Mortality in Deeply Comatose Patients with Spontaneous Cerebellar Hemorrhage.

Abstract: Cerebellar hemorrhage is regarded as a neurosurgical emergency. However, patients with deteriorating consciousness are very likely to die irrespective of the choice of therapy, and it is not clear if surgical intervention can benefit patients in a deeply comatose state. We reviewed 20 patients with a Glasgow Coma Scale score of 3 at admission to ascertain the salvage rate and determine the prognostic factors. Four patients who were managed conservatively died within 2 days. Sixteen patients underwent decompres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 21 publications
2
22
0
5
Order By: Relevance
“…11,12 In some cases, even patients with fixed and dilated pupils or other absent brainstem reflexes have recovered. 32 In the series of Hornig et al, 13 38% of comatose patients achieved a good recovery (nondisabled at hospital discharge) after decompressive surgery. In the German -Austrian Cerebellar Infarction Study, half of all patients who deteriorated into coma and were treated with ventricular drainage or decompressive craniotomy experienced a meaningful recovery (modified Rankin score of 2 or less).…”
Section: What Constitutes Futility?mentioning
confidence: 95%
“…11,12 In some cases, even patients with fixed and dilated pupils or other absent brainstem reflexes have recovered. 32 In the series of Hornig et al, 13 38% of comatose patients achieved a good recovery (nondisabled at hospital discharge) after decompressive surgery. In the German -Austrian Cerebellar Infarction Study, half of all patients who deteriorated into coma and were treated with ventricular drainage or decompressive craniotomy experienced a meaningful recovery (modified Rankin score of 2 or less).…”
Section: What Constitutes Futility?mentioning
confidence: 95%
“…6). 132 Kirollos, et al, 70 prospectively applied a management protocol in 50 consecutive patients with spontaneous cerebellar hemorrhage. They found that evacuation may not be required for hematomas greater than 3 cm if the fourth ventricle was not completely obliterated, but that conscious patients with fourth ventricular obliteration should undergo emergency clot evacuation.…”
mentioning
confidence: 99%
“…Immediate surgical relief of brainstem compression is the primary factor for reducing the mortality rate even in deeply comatose patients. 19) In our series, low preoperative GCS, large hematoma, greater hematoma volume, and brainstem compression were significant factors for poor outcome.…”
Section: Discussionmentioning
confidence: 48%